Ethical Issues in Forensic Psychology Practice: A Systematic Review and Bibliometric Analysis - Arellano, Luz Adriana (Consorcio de Universidades Mexicanas A.C., 2021)
Forensic psychologists confront a myriad of ethical issues and are presented with special challenges to professional training and performance in the field. This study aims to identify the primary ethical issues facing forensic psychology and to carry out a bibliometric study focused on specialized literature ranging from 2010 to 2019. Furthermore, this study examines the state of forensic psychology from an international perspective. A systematic review was conducted following PRISMA standard recommendations. The search began from a pool of 7889 publications, from which were extracted 197 articles, selecting 16 for this study. A total of 124 ethical issues were identified, and they were resumed in 77, which were then classified into six categories: 1) objectivity, 2) intervention, 3) conflict of interest, 4) obtaining and use of information, 5) consent, and 6) professional competence. The bibliometric analysis identified that half of the manuscripts originated from the United States of America with none published in Latin America. Similarly, 87% were published in the English language with 12.5% published in Spanish. However, the Annals of Legal Psychology (Anuario de Psicología Jurídica) published most of the identified dilemmas. Psychology Injury and Law represented the journal with the most publications; the greatest number of articles were published in 2014. The bibliometric analysis suggests studies focused on dilemmas in forensic psychology are scarce and none were found to have been carried out in Mexico.